Representation of harmonic cycles of Modis time series for the analysis of sugarcane cultivation - Antunes, João Francisco Gonçalves; Lamparelli, Rubens Augusto Camargo; Rodrigues, Luiz Henrique Antunes (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate sugarcane cultivation, in a harmonic analysis applied to a time series of Modis vegetation indices, with the representation of harmonic terms. Daily rainfall data were obtained from Agritempo for the state of São Paulo, Brazil, and accumulated for a period of 16 days of Modis compositions, from the 2004/2005 to 2011/2012 crop seasons. The normalized difference vegetation index (NDVI) and the enhanced vegetation index (EVI) were used in time-series decomposed in harmonic terms by the harmonic analysis. In order to visualize the growing conditions of vegetation in agricultural areas, specially the phase information, the HLS transformation was applied to the harmonic terms obtained by the Hants algorithm, using Envi software. Sugarcane cultivation in the state of São Paulo shows spatial patterns that are coherent with the sugarcane development cycle and consistent with the variability of seasonal rainfall that directly affect the maximum period of vegetation indices. The peak growth stage of sugarcane occurs in years of normal rainfall; however, in years with below normal rainfall, sugarcane maturation phase is anticipated, and, in years with above normal rainfall, the growth phase is anticipated, which causes maturation delay.